PELANGGARAN PENGATURAN PRINSIP MIRANDA RULE DALAM HUKUM ACARA PIDANA INDONESIA - SITORUS, FINTA RIRIS; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Miranda Rule is a rule to manage about the suspect rights before investigation by police. Miranda rule consist from the right to silence, because everything what the suspect said can damning in court. The right to get the lawyer to defend the suspect right, and if the suspect not competent, so the suspect can get the lawyer by the government. But, in fact the suspect never directly get notified about the right and the police looks like ignore the suspect rights especially the rights to silence.In this case, related to violation principle of miranda rule in Indonesia criminal justice system, the effect violation principle of miranda rule and prevention principle of miranda rule. The purpose of this thesis, First, violation principle of miranda rule in Indonesia criminal justice system and the effect to the violation principle of miranda rule. Second, the prevention principle of miranda rule in Indonesia criminal justice system. The type of this research be classified as normative research, because this research review the violation principle of miranda rule based on the applicable regulation. The data based on secondary data, and the collecting data technical in this research consist of library research study case.There are two main idea can be resumed. First, there are many violation principle of miranda rule from investigation until to the court. This rule always broke by investigator and prosecutor that effect the arresting is illegal and the investigation announcement not to be valid. So, prosecution process can not be accept, include the accusation because it was arrange by the invalid investigation announcement. It means the suspect must be released from the prison. Second, the prevention violation principle of miranda rule can be minimize by maximize the human resources quality in principle of miranda rule establishment so the police can understanding how to implementation principle of miranda rule in fact. The author suggestion, First, there are need to explain the principle of miranda rule in Indonesi criminal justice system and other rule, and giving a strict sanctions for everything violation principle o miranda rule. Second, there are need to maximize the profesional of law agency by maximize the education quality, especially for founding and training in law aspect.Keywords: Miranda Rule, The Right to Silence, Criminal Justice System